Anisotropic mechanical and functional properties of graphene-based alumina matrix nanocomposites. Issue 8 (July 2016) - Çelik, Y.; Çelik, A.; Flahaut, E.; Suvaci, E.
Abstract: Graphene platelets (GPLs) containing Al2 O3 nanocomposites, which exhibit anisotropic microstructure, have been prepared by spark plasma sintering (SPS), and effects of this anisotropy on mechanical, electrical and thermal properties of the nanocomposites have been investigated. 3 vol.% GPLs addition into monolithic Al2 O3 caused fracture toughness ( K ıc ) to increase by 26.7% in the in-plane direction and to decrease by 17.2% in the through thickness direction. K ıc started to decrease in the in-plane direction and to increase in the through-thickness direction with further increase in the GPLs amount. The electrical conductivity of the nanocomposites exhibited a slight anisotropy with a lower resistivity in the in-plane direction. Oriented GPLs also led to a less resistive heat conduction path in the in-plane direction. ∼44% increase in the in-plane thermal conductivity was achieved at 600 °C with 15 vol.% GPLs addition into the monolithic Al2 O3 and this resulted in ∼52% increase in the k in-plane / k through-thickness ratio.